Short- and long-term allocation of power in liberalized electricity markets - Torgeir Ericson; Bente Halvorsen (Statistics Norway, Research Department, 2010)
The experience of liberalized electricity markets' ability to allocate scarce energy resources has been mixed. In this paper, we analyze how liberalized markets allocate power in the short and long run through the interaction between the spot and end-user markets. We show that totally inelastic demand in the spot market does not necessarily result in market failure in a shortage situation, as long as price incentives are transferred to the end-user markets. We argue that the market does not have to run optimally to handle a shortage situation, and that problems with short- or long-run allocation of power arise when price restrictions in end-user markets results in a higher demand than that which may sustain the energy situation over time.
Keywords: D4; Q4; 330; Liberalized electricity market; allocation of power; demand response